2020
DOI: 10.1161/circimaging.120.011526
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Magnetic Resonance Imaging Strain Predicts the Onset of Duchenne Muscular Dystrophy–Associated Cardiomyopathy

Abstract: Background: Early detection of left ventricular (LV) dysfunction before the onset of overt Duchenne muscular dystrophy–associated cardiomyopathy (DMDAC) may direct clinical management to slow onset of dysfunction. We aimed to assess whether LV strain will predict those who develop DMDAC. Methods: We performed a single center retrospective case control study of patients with Duchenne muscular dystrophy who underwent serial cardiac magnetic resonance betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…Though the values for these volumetric and mass parameters were lower than the unaffected population, they were still within the normal range except for LVEDV. Our results agree with previous cross sectional studies [27,28,32,48] which have found composite circumferential strain on tagged and CINE images (using feature tracking) strain to be significantly worse in comparison to healthy controls and to be affected earlier in the disease process prior to structural remodeling [28,49]. These findings emphasize the importance of measuring strain in this patient population at an early stage of the disease.…”
Section: Strain and Volumetric Cardiac Function Decline In Dmdsupporting
confidence: 91%
See 2 more Smart Citations
“…Though the values for these volumetric and mass parameters were lower than the unaffected population, they were still within the normal range except for LVEDV. Our results agree with previous cross sectional studies [27,28,32,48] which have found composite circumferential strain on tagged and CINE images (using feature tracking) strain to be significantly worse in comparison to healthy controls and to be affected earlier in the disease process prior to structural remodeling [28,49]. These findings emphasize the importance of measuring strain in this patient population at an early stage of the disease.…”
Section: Strain and Volumetric Cardiac Function Decline In Dmdsupporting
confidence: 91%
“…Based on these limitations, there is a need to develop cardiac assessment tools that are non-invasive, safe, and sensitive to detect cardiac dysfunction at an early stage [2,3,19,25,26]. Various non-invasive techniques such as circumferential strain using tagged and feature tracking techniques, T1 mapping, and change in volumetric functions have been used to quantify disease progression in DMD [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular manifestations of DMD vary and include dilated cardiomyopathy, arrhythmias, and congestive heart failure 4,5 . Because cardiovascular events frequently occur during DMD progression, non‐invasive imaging techniques and laboratory tests can help identify patients at risk of clinical deterioration and assess treatment response 6–10 . However, early prediction of disease progression for DMD is challenging despite emphasizing the increased mortality rate of DMD patients due to cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Because cardiovascular events frequently occur during DMD progression, non‐invasive imaging techniques and laboratory tests can help identify patients at risk of clinical deterioration and assess treatment response. 6 , 7 , 8 , 9 , 10 However, early prediction of disease progression for DMD is challenging despite emphasizing the increased mortality rate of DMD patients due to cardiomyopathy. However, despite emphasizing the increased mortality rate of DMD patients due to cardiomyopathy, early prediction of disease progression for DMD is challenging due to the rarity of DMD 11 and the difficulty of gathering data to investigate long‐term effects regarding left ventricular systolic functions.…”
Section: Introductionmentioning
confidence: 99%